The acrobat & the angel - Shannon, Mark; Shannon, David 1959-. (New York Penguin Group, 1999)
After his grandmother dies, a boy with a talent as an acrobat finds a home at a monastery where he must give up his "carnival ways"--until he performs one last miraculous time.
Puffin books.
Ages 4-8.
Keywords: Folklore -- France